On the Conceivability of a Cognitive Phenomenology Zombie. (21st July 2019) - Fürst, Martina
Abstract: The cognitive phenomenology thesis has it that conscious cognitive states essentially exhibit a phenomenal character. Defenders of 'conservatism' about cognitive phenomenology think that the phenomenology of thought is reducible to sensory phenomenology. In contrast, proponents of 'liberalism' hold that there is a proprietary, sui generis cognitive phenomenology. Horgan develops a morph‐sequence argument to argue for liberalism. The argument is based on the conceivability of a cognitive phenomenology zombie, i.e. a man who does not understand Chinese but shares the behavior and sensory phenomenology with his twin who does understand Chinese. I argue that the conceivability of a cognitive phenomenology‐zombie fails to settle the debate between conservatives and liberals. The roots of the ineffectiveness of the argument lie in the diverse readings of sensory phenomenology which flesh out the relation between sensory phenomenology and concepts differently but explain the conceivability of the scenario equally well. The lesson to learn is that to adjudicate the debate about cognitive phenomenology, we first have to clarify the notion of sensory phenomenology.